Peran Pembiasaan Kedisiplinan Terhadap Karakter Anak Usia 4-5 Tahun di KB Aisyiyah 1 Sadang - Linasih, Retno; Hidayah, Nahdiyah (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
This research aims to understand the impact of increasing discipline on students through habituation activities carried out at KB Aisyiyah 1 Sadang. Children need to get used to character formation from an early age, including the character of discipline in children that needs to be developed. One way is through habituation. This type of research is qualitative research. The data collection method used is interviews, observation and documentation. The results of this research show the development of disciplinary attitudes in children, although there are still some children who are not yet capable of discipline, but in general this habit of discipline shows a positive impact on student discipline.